PROMIS Burkina Faso Follow-Up Data of the Longitudinal Study 2015-2017, Child*Month*Platform Level - International Food Policy Research Institute; AfricSanté (International Food Policy Research Institute, 2019)
The dataset contains longitudinal data ( child*month*Platform follow-up) of the impact evaluation in Burkina Faso of the “Innovative Approaches for the Prevention of Childhood Malnutrition” (PROMIS) project, which integrated a preventive intervention package into Community Management for Acute Malnutrition (CMAM) programming in Burkina Faso and Mali. Using cluster randomized designs, we evaluated the impact of integrating preventive services into screening for child acute malnutrition on acute malnutrition screening and treatment coverage and acute malnutrition prevalence and incidence. The PROMIS program sought to address the low screening coverage in Burkina Faso by integrating two preventive interventions into the screening at monthly well-baby consultations offered at the health center: (1) behavior change communication on essential nutrition and hygiene actions to improve child nutrition and health-seeking behavior, including for malnutrition; (2) the provision of a small-quantity lipid-based nutrient supplement (SQ-LNS) to all children to increase intake of essential nutrients (and prevent undernutrition) and to incentivize caregivers to participate regularly in acute malnutrition screening. The intervention was implemented by Helen Keller International through the national health system. Data were collected by the International Food Policy Research Institute (IFPRI) in collaboration with AfricSanté.